NCERT Solutions for Class 7 Maths Exercise 1.4 Chapter 1 Integers are available here in simple PDF. This exercise of NCERT Solutions for Class 7 Maths Chapter 1 has topics related to the division of Integers. The division is the inverse operation of multiplication. This exercise also deals with the properties of the division of Integers. Students are suggested to solve the questions from NCERT Solutions for Class 7 Maths Chapter 1 Integers to score good marks in the final exams.

## Download the PDF of NCERT Solutions for Class 7 Maths Chapter 1 Integers – Exercise 1.4

### Access Answers to NCERT Class 7 Maths Chapter 1 – Integers Exercise 1.4

**1. Evaluate each of the following:**

**(a) (-30) ÷ 10 **

**Solution:-**

= (-30) ÷ 10

= – 3

When we divide a negative integer by a positive integer, we first divide them as whole numbers and then put the minus sign (-) before the quotient.

**(b) 50 ÷ (-5) **

**Solution:-**

= (50) ÷ (-5)

= – 10

When we divide a positive integer by a negative integer, we first divide them as whole numbers and then put the minus sign (-) before the quotient.

**(c) (-36) ÷ (-9)**

**Solution:-**

= (-36) ÷ (-9)

= 4

When we divide a negative integer by a negative integer, we first divide them as whole numbers and then put the positive sign (+) before the quotient.

**(d) (–49) ÷ (49) **

**Solution:-**

= (–49) ÷ 49

= – 1

When we divide a negative integer by a positive integer, we first divide them as whole numbers and then put the minus sign (-) before the quotient.

**(e) 13 ÷ [(–2) + 1] **

**Solution:-**

= 13 ÷ [(-2) + 1]

= 13 ÷ (-1)

= – 13

When we divide a positive integer by a negative integer, we first divide them as whole numbers and then put the minus sign (-) before the quotient.

**(f) 0 ÷ (-12)**

**Solution:-**

= 0 ÷ (-12)

= 0

When we divide zero by a negative integer gives zero.

**(g) (–31) ÷ [(–30) + (–1)]**

**Solution:-**

= (–31) ÷ [(–30) + (–1)]

= (-31) ÷ [-30 – 1]

= (-31) ÷ (-31)

= 1

When we divide a negative integer by a negative integer, we first divide them as whole numbers and then put the positive sign (+) before the quotient.

**(h) [(–36) ÷ 12] ÷ 3**

**Solution:-**

First, we have to solve the integers within the bracket,

= [(–36) ÷ 12]

= (–36) ÷ 12

= – 3

Then,

= (-3) ÷ 3

= -1

When we divide a negative integer by a positive integer, we first divide them as whole numbers and then put the minus sign (-) before the quotient.

**(i) [(– 6) + 5)] ÷ [(–2) + 1]**

**Solution:-**

The given question can be written as,

= [-1] ÷ [-1]

= 1

When we divide a negative integer by a negative integer, we first divide them as whole numbers and then put the positive sign (+) before the quotient.

**2. Verify that a ÷ (b + c) ≠ (a ÷ b) + (a ÷ c) for each of the following values of a, b and c.**

**(a) a = 12, b = -4, c = 2**

**Solution:-**

From the question, a ÷ (b + c) ≠ (a ÷ b) + (a ÷ c)

Given, a = 12, b = – 4, c = 2

Now, consider LHS = a ÷ (b + c)

= 12 ÷ (-4 + 2)

= 12 ÷ (-2)

= -6

When we divide a positive integer by a negative integer, we first divide them as whole numbers and then put the minus sign (-) before the quotient.

Then, consider RHS = (a ÷ b) + (a ÷ c)

= (12 ÷ (-4)) + (12 ÷ 2)

= (-3) + (6)

= 3

By comparing LHS and RHS

= -6 ≠ 3

= LHS ≠ RHS

Hence, the given values are verified.

**(b) a = (–10), b = 1, c = 1**

**Solution:-**

From the question, a ÷ (b + c) ≠ (a ÷ b) + (a ÷ c)

Given, a = (-10), b = 1, c = 1

Now, consider LHS = a ÷ (b + c)

= (-10) ÷ (1 + 1)

= (-10) ÷ (2)

= -5

Then, consider RHS = (a ÷ b) + (a ÷ c)

= ((-10) ÷ (1)) + ((-10) ÷ 1)

= (-10) + (-10)

= -10 – 10

= -20

By comparing LHS and RHS

= -5 ≠ -20

= LHS ≠ RHS

Hence, the given values are verified.

**3. Fill in the blanks:**

**(a) 369 ÷ _____ = 369 **

**Solution:-**

Let us assume the missing integer is x,

Then,

= 369 ÷ x = 369

= x = (369/369)

= x = 1

Now, put the valve of x in the blank.

= 369 ÷ 1 = 369

**(b) (–75) ÷ _____ = –1**

**Solution:-**

Let us assume the missing integer is x,

Then,

= (-75) ÷ x = -1

= x = (-75/-1)

= x = 75

Now, put the valve of x in the blank.

= (-75) ÷ 75 = -1

**(c) (–206) ÷ _____ = 1 **

**Solution:-**

Let us assume the missing integer is x,

Then,

= (-206) ÷ x = 1

= x = (-206/1)

= x = -206

Now, put the valve of x in the blank.

= (-206) ÷ (-206) = 1

**(d) – 87 ÷ _____ = 87**

**Solution:-**

Let us assume the missing integer is x,

Then,

= (-87) ÷ x = 87

= x = (-87)/87

= x = -1

Now, put the valve of x in the blank.

= (-87) ÷ (-1) = 87

**(e) _____ ÷ 1 = – 87 **

**Solution:-**

Let us assume the missing integer is x,

Then,

= (x) ÷ 1 = -87

= x = (-87) × 1

= x = -87

Now, put the valve of x in the blank.

= (-87) ÷ 1 = -87

**(f) _____ ÷ 48 = –1**

**Solution:-**

Let us assume the missing integer is x,

Then,

= (x) ÷ 48 = -1

= x = (-1) × 48

= x = -48

Now, put the valve of x in the blank.

= (-48) ÷ 48 = -1

**(g) 20 ÷ _____ = -2 **

**Solution:-**

Let us assume the missing integer is x,

Then,

= 20 ÷ x = -2

= x = (20)/ (-2)

= x = -10

Now, put the valve of x in the blank.

= (20) ÷ (-10) = -2

**(h) _____ ÷ (4) = –3**

**Solution:-**

Let us assume the missing integer is x,

Then,

= (x) ÷ 4 = -3

= x = (-3) × 4

= x = -12

Now, put the valve of x in the blank.

= (-12) ÷ 4 = -3

**4. Write five pairs of integers (a, b) such that a ÷ b = –3. One such pair is (6, –2) because 6 ÷ (–2) = (–3).**

**Solution:-**

(i) (15, -5)

Because, 15 ÷ (–5) = (–3)

(ii) (-15, 5)

Because, (-15) ÷ (5) = (–3)

(iii) (18, -6)

Because, 18 ÷ (–6) = (–3)

(iv) (-18, 6)

Because, (-18) ÷ 6 = (–3)

(v) (21, -7)

Because, 21 ÷ (–7) = (–3)

**5. The temperature at 12 noon was 10 ^{o}C above zero. If it decreases at the rate of 2^{o}C per hour until midnight, at what time would the temperature be 8°C below zero? What would be the temperature at midnight?**

**Solution:-**

From the question, given that,

The temperature at the beginning, i.e. at 12 noon = 10^{o}C

Rate of change of temperature = – 2^{o}C per hour

Then,

Temperature at 1 p.m. = 10 + (-2) = 10 – 2 = 8^{o}C

Temperature at 2 p.m. = 8 + (-2) = 8 – 2 = 6^{o}C

Temperature at 3 p.m. = 6 + (-2) = 6 – 2 = 4^{o}C

Temperature at 4 p.m. = 4 + (-2) = 4 – 2 = 2^{o}C

Temperature at 5 p.m. = 2 + (-2) = 2 – 2 = 0^{o}C

Temperature at 6 p.m. = 0 + (-2) = 0 – 2 = -2^{o}C

Temperature at 7 p.m. = -2 + (-2) = -2 -2 = -4^{o}C

Temperature at 8 p.m. = -4 + (-2) = -4 – 2 = -6^{o}C

Temperature at 9 p.m. = -6 + (-2) = -6 – 2 = -8^{o}C

∴ At 9 p.m., the temperature will be 8^{o}C below zero

Then,

The temperature at midnight, i.e. at 12 a.m.

Change in temperature in 12 hours = -2^{o}C × 12 = – 24^{o}C

So, at midnight temperature will be = 10 + (-24)

= – 14^{o}C

So, at midnight temperature will be 14^{o}C below 0.

**6. In a class test, (+3) marks are given for every correct answer and (-2) marks are given for every incorrect answer and no marks for not attempting any question. (i) Radhika scored 20 marks. If she has got 12 correct answers, how many questions has she attempted incorrectly? (ii) Mohini scored –5 marks in this test, though she got 7 correct answers. How many questions has she attempted incorrectly?**

**Solution:-**

From the question,

Marks awarded for 1 correct answer = +3

Marks awarded for 1 wrong answer = -2

(i) Radhika scored 20 marks

Then,

Total marks awarded for 12 correct answers = 12 × 3 = 36

Marks awarded for incorrect answers = Total score – Total marks awarded for 12 correct

Answers

= 20 – 36

= – 16

So, the number of incorrect answers made by Radhika = (-16) ÷ (-2)

= 8

(ii) Mohini scored -5 marks

Then,

Total marks awarded for 7 correct answers = 7 × 3 = 21

Marks awarded for incorrect answers = Total score – Total marks awarded for 12 correct

Answers

= – 5 – 21

= – 26

So, the number of incorrect answers made by Mohini = (-26) ÷ (-2)

= 13

**7. An elevator descends into a mine shaft at the rate of 6 m/min. If the descent starts from 10 m above the ground level, how long will it take to reach – 350 m?**

**Solution:-**

From the question,

The initial height of the elevator = 10 m

The final depth of the elevator = – 350 m … [∵distance descended is denoted by a negative

integer]

The total distance to descended by the elevator = (-350) – (10)

= – 360 m

Then,

Time taken by the elevator to descend -6 m = 1 min

So, the time taken by the elevator to descend – 360 m = (-360) ÷ (-60)

= 60 minutes

= 1 hour

Thanks for byjus

Suberb app